Research and Development in Intelligent Systems XXVIII 2011
DOI: 10.1007/978-1-4471-2318-7_18
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network for Counter-Terrorism

Abstract: This article presents findings concerned with the use of neural networks in the identification of deceptive behaviour. A game designed by psychologists and criminologists was used for the generation of data used to test the appropriateness of different AI techniques in the quest for counter-terrorism. A feed forward back propagation network was developed and subsequent neural network experiments showed on average a 60% success rate and at best a 68% success rate for correctly identifying deceptive behaviour. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In every country, dealing with terrorism is the top most priority of the government. ey seek for techniques to Input: the whole dataset of GTD along with labels Output: optimized values of W and b Data: GTD Datasets (1) W [1..L] � random numbers //Glorot Uniform initializer (2) b [1..L] � random numbers (3) while i ≤ num iteration do (4) k ⟵ 1 (5) while j ≤ L do (6) Z [j] � W [j]T .A [j− 1] + b [j] 7A [j] � g(Z [j] )//g(Z) � max(0, z) (8) increment j by 1 (9) L(A [L] , Y) � − (1/m) m i�0 Y i log(A [L] i ) //Binary cross-entropy loss (10) k ⟵ L (11) while k ≥ 0 do (12) W [k] � W [k] − αzL/zW[k] (13) b [k] � b [k] − αzL/zb[k] (14) decrement k by 1 ALGORITHM 2: e training of deep neural network using gradient descent optimization algorithm. Complexity understand the different factors involved in terrorism and how to deal with those factors in order to completely stop or reduce terrorist activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In every country, dealing with terrorism is the top most priority of the government. ey seek for techniques to Input: the whole dataset of GTD along with labels Output: optimized values of W and b Data: GTD Datasets (1) W [1..L] � random numbers //Glorot Uniform initializer (2) b [1..L] � random numbers (3) while i ≤ num iteration do (4) k ⟵ 1 (5) while j ≤ L do (6) Z [j] � W [j]T .A [j− 1] + b [j] 7A [j] � g(Z [j] )//g(Z) � max(0, z) (8) increment j by 1 (9) L(A [L] , Y) � − (1/m) m i�0 Y i log(A [L] i ) //Binary cross-entropy loss (10) k ⟵ L (11) while k ≥ 0 do (12) W [k] � W [k] − αzL/zW[k] (13) b [k] � b [k] − αzL/zb[k] (14) decrement k by 1 ALGORITHM 2: e training of deep neural network using gradient descent optimization algorithm. Complexity understand the different factors involved in terrorism and how to deal with those factors in order to completely stop or reduce terrorist activities.…”
Section: Resultsmentioning
confidence: 99%
“…e authors demonstrated that ensemble framework has better figures compared to individual models. In 2011, Dixon et al [14] developed a neural network-based framework for counterterrorism. e authors used a game that is designed by criminologist and psychologists to generate data that can test 2 Complexity the suitability of AI techniques to look for counterterrorism.…”
Section: Related Workmentioning
confidence: 99%
“…The scholarship on a terrorist network has witnessed a manifold increase in recent times, especially concerning gaining insight into a terrorist network. Diverse approaches to understanding terrorism such as the use of AI [24], including the CNN model [29], ], machines learning [25], [26], [27], [31], and natural language processing [28] have all been applied. The work in [20] suggests the aggregation of knowledge from diverse sources in solving complex issues collectively.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the occurrence was far from random and had a periodicity of around 1 month, but the victimization rate had no constant trend. Moreover, in [13], the authors highlighted the importance of neural networks in predicting terrorism behavior. A game was designed by criminologists and psychologists to test the effectiveness of different AI technologies/algorithms.…”
Section: Related Workmentioning
confidence: 99%